Disseminated BCG infection in a child with multifocal osteomyelitis due to STAT1 LOF variant and primary immunodeficiency disease was significantly improved after anti-tuberculosis treatment: a case report - Ouyang, Haiping; Yang, Di; Wang, Zhongliang (Frontiers in Pediatrics, 2025)
BackgroundThis was a rare case where the diagnosis was not obvious during treatment, but the treatment was effective after diagnosis. An infant with recurrent fever was considered for systemic multiple osteomyelitis after two surgical biopsies. After a third operation to take a lymph node biopsy, the patient was finally diagnosed as having disseminated Bacille Calmette-Guerin(BCG) disease caused by BCG vaccination. After diagnosis, the child was effectively treated with anti-tuberculosis therapy.Case descriptionA 2-month-old female patient was hospitalized twice for fever and surface mass. The patient underwent a puncture biopsy of the right tibia and a puncture biopsy of the lesion of the right leg respectively. The patient was diagnosed with systemic multiple osteomyelitis. The patient still had recurrent fever after antibiotic treatment. At outpatient follow-up, the patient was found to have primary immunodeficiency disease with STAT1 LOF mutation. When the child was one year and one month old, she was hospitalized again with a fever. The patient underwent a third operation, a biopsy of the left axillary lymph node. The pathological results suggested granulomatous inflammation, which was considered tuberculosis. The child was diagnosed with disseminated BCG vaccine disease. After 16 months of oral treatment with isoniazid, rifampicin, ethambutol,and levofloxacin, the child's condition was significantly improved.ConclusionsThe performance of multiple surgical biopsies is crucial in cases of infants presenting with recurrent fever and widespread bone destruction, as well as in children diagnosed with primary immunodeficiency disease, particularly when the available etiological tests offer limited diagnostic evidence.